Hyperbaric oxygen-induced acute lung injury: A mouse model study on pathogenic characteristics and recovery dynamics - Wang, Shu; Chen, Hong; Li, Zhi; Xu, Guangxu; Bao, Xiaochen (Frontiers in Physiology, 2024)
Oxygen is an essential substance for the maintenance of human life. It is also widely used in clinical and diving medicine. Although oxygen is crucial for survival, too much oxygen can be harmful. Excessive oxygen inhalation in a short period of time can lead to injury, and the lung is one of the main target organs. Acute lung injury (ALI) induced by hyperbaric oxygen (HBO) is notably more severe than that caused by normobaric oxygen, yet systematic research on such injury and its regression is scarce. In this study, two independent experiments were designed. In the first experiment, mice were exposed to 2 atmospheres absolute (ATA), ≥95% oxygen for 2, 4, 6, and 8 h. Changes in lung histopathology, inflammation and expression of chemokines, alveolar-capillary barrier, and 8-OHdG were detected before and after the exposure. In the second experiment, these parameters were measured at 0 h, 12 h, and 24 h following 6 h of exposure to 2 ATA of ≥95% oxygen. Research indicates that ALI induced by HBO is characterized histologically by alveolar expansion, atelectasis, inflammatory cell infiltration, and hemorrhage. At 2 ATA, significant changes in the alveolar-capillary barrier were observed after more than 95% oxygen exposure for 4 h, as evidenced by increased Evans blue (EB) extravasation (p = 0.0200). After 6 h of HBO exposure, lung tissue pathology scores, 8-OHdG levels, and inflammatory and chemotactic factors (such as Il6, CCL2, CCL3, CXCL5, and CXCL10), intercellular adhesion molecule 1 (ICAM1), and vascular cell adhesion molecule 1 (VCAM1) were significantly elevated. Compared to lung injury caused by normobaric oxygen, the onset time of injury was significantly shortened. Additionally, it was observed that these markers continued to increase after leaving the HBO environment, peaking at 12 h and starting to recover at 24 h, indicating that the peak of inflammatory lung injury occurs within 12 h post-exposure, with recovery beginning at 24 h. This contradicts the common belief that lung injury is alleviated upon removal from a high-oxygen environment. However, EB levels, which reflect damage to the alveolar-capillary barrier, and VE-Cadherin (VE-Cad), tight junction protein 1 (ZO-1), ICAM1, and VCAM1 remained significantly altered 24 h after leaving the HBO environment. This suggests that the alveolar-capillary barrier is the most sensitive and slowest recovering part of the lung injury induced by HBO. These findings can provide insights into the pathogenesis and progression of lung injury caused by HBO and offer references for identifying corresponding intervention targets.